2013
DOI: 10.1111/eje.12045
|View full text |Cite
|
Sign up to set email alerts
|

A review of continuing professional development for dentists in Europe*

Abstract: Aim:  To summarise findings from a literature review of dentists’ engagement in continuing professional development (CPD) and its effects on improving oral health care for patients. Method:  The search strategy used key terms in a range of databases and an academic literature search engine, complemented by hand searching and citation follow‐up. Results:  One hundred and fourteen papers were reviewed. The majority of dentists engaged in CPD. Factors affecting participation included time since graduation, costs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…Continuing professional development (CPD) has been defined by the European commission as 'a career-long process required by dentists to maintain, update, and broaden their attitudes, knowledge, and skills in a way that will bring the greatest benefit to their patients' (4). CPD is now recognized as an essential professional activity for dentists to maintain their clinical skills and to keep up to date with new developments in scientific knowledge and technology and to integrate these techniques into clinical practice safely (5)(6)(7)(8)(9)(10)(11)(12). This is particularly important in implant dentistry, as techniques and materials develop at a fast rate due to rapid advances in biomedical technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing professional development (CPD) has been defined by the European commission as 'a career-long process required by dentists to maintain, update, and broaden their attitudes, knowledge, and skills in a way that will bring the greatest benefit to their patients' (4). CPD is now recognized as an essential professional activity for dentists to maintain their clinical skills and to keep up to date with new developments in scientific knowledge and technology and to integrate these techniques into clinical practice safely (5)(6)(7)(8)(9)(10)(11)(12). This is particularly important in implant dentistry, as techniques and materials develop at a fast rate due to rapid advances in biomedical technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the DentCPD project investigated the CPD requirements for dentists in Europe (9)(10)(11). This demonstrated that only about half of the European countries had a compulsory CPD system that included mandatory core topics.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used to support the development of these guidelines consisted of an extensive literature inventory (4), a survey of existing (EU and global) practices in dental CPD (5), a survey and discussions amongst ADEE meeting attendants and debate amongst the DentCPD project team which led to a consensus.…”
Section: Methodsmentioning
confidence: 99%
“…In general, excepting structured degree programmes leading to an academic title and/or specialty, there are three types of CPD activity commonly available to dentists: (i) reading professional journals; (ii) attending lectures, courses or study clubs and (iii) undertaking short-term or modular training courses to learn new techniques (7)(8)(9). To have any real impact on clinical practice, CPD activity should be systematically planned and structured in relation to the specific learning needs of the individual clinician and not selected arbitrarily according to ease of access or convenience.…”
Section: Introductionmentioning
confidence: 99%
“…In general, university dental schools and professional dental associations were found to be the most common CPD providers, which reportedly provided the best quality of teaching. The need for harmonisation of CPD across Europe to support the safe management of patients and promote mobility of practitioners was recommended on the basis of the findings of the DentCPD survey (9,10).…”
Section: Introductionmentioning
confidence: 99%